Foreign direct investment : analysis of aggregate flows - Razin, Assaf; Sadka, Efraim (Princeton University Press, 2007)
The 1990s saw global flows of foreign direct investment increase some sevenfold, spurring economists to explore FDI from a micro- or trade-based perspective. Foreign Direct Investment is one of the first books to analyze the macroeconomics of FDI, treating FDI as a unique form of international capital flow between specific pairs of countries. By examining the determinants of the aggregate flows of FDI at the bilateral, source-host-country level, Assaf Razin and Efraim Sadka present the first systematic global analysis of the singular features of FDI flows. Drawing on a wealth of fresh data, th.